9514 1404 393
Answer:
16.4
Step-by-step explanation:
The law of cosines is useful here. It tells you ...
b^2 = a^2 + c^2 -2ac·cos(B)
b^2 = 22^2 +10^2 -2·22·10·cos(44°)
b^2 ≈ 267.49
b ≈ √267.49 ≈ 16.35514
b ≈ 16.4
Step 1: Simplify both sides of the equation.
−36=p−30
Step 2: Flip the equation.
p−30=−36
Step 3: Add 30 to both sides.
p−30+30=−36+30
p=−6
2(2x+3)+(5x+4) simplified would be 4x+6+5x+4 and if you add those together you get 9x+10. Hope I helped! if you have any questions just leave a comment